THE INFLUENCE OF WORK MOTIVATION AND LOYALTY BEHAVIOR ON THE PERFORMANCE OF STATE CIVIL SERVANT EMPLOYEES IN THE REGIONAL SECRETARIAT OF NORTH SUMATRA PROVINCE - Safariani, Dewi; Lumbanraja, Prihatin; Siahaan, Elisabet (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to examine the influence of work motivation and loyalty behavior on the performance of state civil servants in the Regional Secretariat of North Sumatra Province. The sampling technique used the saturated sampling technique with a total sample of 43 employees. Data analysis in this study uses Multiple Linear Regression Analysis. The results showed that work motivation had a positive and significant effect on the Performance of State Civil Servant Employees in the Regional Secretariat of North Sumatra Province. Loyalty behavior had a positive and significant impact on the Performance of State Civil Servant Employees in the Regional Secretariat of North Sumatra Province.